Future jamming: Rhetoric of new knowledge in Finnish educational policy texts. Issue 7 (October 2021) - Säntti, Janne; Hansen, Petteri; Saari, Antti
The future is rarely problematised in education even though it is self-evident in everyday schoolwork and present also in the management of education. However, we should understand how different future visions influence our understanding of education. In this paper, we apply rhetorical analysis and study how the future of education is rhetorically constructed in Finnish policy texts. Also, we analyze the special characteristic of Finnish future visions, which are based on the idea of Finnish education being top-notch. We focus explicitly on the idea of knowledge and its future relations in school education. In our data, the current school is rhetorically contrasted with the future one. This hastens the need to modernize Finnish school system. This view is reinforced by the needs of the economy and working life. Pathos is frequently used as a rhetorical strategy. Finns are warned about remaining in the past and obliged to change their education immediately. Future visions of Finnish education seem to be limited only to positive aspects.